Tres generaciones: Kim Ji Young, nacida en 1982 como un prisma para comprender la construcción de la individualidad de las mujeres en Corea del Sur (2022)
This article presents a research study of three generations of women in South Korea. To achieve this goal, Cho Nam-Joo’s bestseller Kim Ji-young: Born 1982 is used as a prism for understanding the evolution of society during the period of transition and settlement of modernity. The sociohistorical analysis was carried out based on the articulation of documentary sources and social theories that allow us to understand the dynamics that took place in women’s trajectories. The results show the process of shaping individuals, the construction and transformation of dreams and aspirations for the future, as well as the crisis of the family and the resignification of work based on the desire for independence and autonomy.